The Culture Environment Influences Both Gene Regulation and Phenotypic Heterogeneity in Escherichia coli - Smith, Ashley; Kaczmar, Agnieszka; Bamford, Rosemary A.; Smith, Christopher; Frustaci, Simona; Kovacs-Simon, Andrea; O’Neill, Paul; Moore, Karen; Paszkiewicz, Konrad; Titball, Richard W.; Pagliara, Stefano (Frontiers in Microbiology, 2018)
Microorganisms shape the composition of the medium they are growing in, which in turn has profound consequences on the reprogramming of the population gene-expression profile. In this paper, we investigate the progressive changes in pH and sugar availability in the medium of a growing Escherichia coli (E. coli) culture. We show how these changes have an effect on both the cellular heterogeneity within the microbial community and the gene-expression profile of the microbial population. We measure the changes in gene-expression as E. coli moves from lag, to exponential, and finally into stationary phase. We found that pathways linked to the changes in the medium composition such as ribosomal, tricarboxylic acid cycle (TCA), transport, and metabolism pathways are strongly regulated during the different growth phases. In order to quantify the corresponding temporal changes in the population heterogeneity, we measure the fraction of E. coli persisters surviving different antibiotic treatments during the various phases of growth. We show that the composition of the medium in which β-lactams or quinolones, but not aminoglycosides, are dissolved strongly affects the measured phenotypic heterogeneity within the culture. Our findings contribute to a better understanding on how the composition of the culture medium influences both the reprogramming in the population gene-expression and the emergence of phenotypic variants.